Molecular cloning of complementary DNAs encoding the heavy chain of the human 4F2 cell-surface antigen: a type II membrane glycoprotein involved in normal and neoplastic cell growth. - Quackenbush, E (1987)
Complementary DNA (cDNA) clones encoding the heavy chain of the heterodimeric human membrane glycoprotein 4F2 have been isolated by immunoscreening of a lambda gt11 expression library. The identity of these clones has been confirmed by hybridization to RNA and DNA prepared from mouse L-cell transfectants, which were produced by whole cell gene transfer and selected for cell-surface expression of the human 4F2 heavy chain. DNA sequence analysis suggests that the 4F2 heavy-chain cDNAs encode an approximately 526-amino acid type II membrane glycoprotein, which is composed of a large C-terminal extracellular domain, a single potential transmembrane region, and a 50-81 amino acid N-terminal intracytoplasmic domain. Southern blotting experiments have shown that the 4F2 heavy-chain cDNAs are derived from a single-copy gene that has been highly conserved during mammalian evolution.